Case Report: A comprehensive digital workflow to enhance predictability and precision with fixed dental prostheses in the posterior region - Toser, Isabela; Faur, Andrei-Bogdan; Anghel-Lorinți, Anca-Elena; Jivănescu, Anca (Frontiers in Dental Medicine, 2025)
This clinical report presents a full digital protocol for prosthetic rehabilitation following the bilateral loss of maxillary first molars. The aim of the study was to explore the integration of advanced digital technologies, including intraoral scanning, facial scanning, cone-beam computed tomography (CBCT), and digital occlusal analysis, into a comprehensive treatment protocol for the fabrication of fixed partial dental prostheses. A key focus was on evaluating the precision of occlusal equilibration using digital occlusal analysers in conjunction with conventional articulating paper. While the design was sent to a dental laboratory for fabrication, the workflow demonstrated efficiency, minimal invasiveness, and a high degree of predictability in achieving both functional and aesthetic outcomes, mostly manageable in a chair-side manner. The results showed that most occlusal contacts translated successfully from virtual planning to the intraoral environment; however, some discrepancies were noted, which could be attributed to the absence of certain motion data in the digital workflow. The integration of digital occlusal analysis was essential in identifying and adjusting premature contacts, contributing to improved patient comfort and occlusal stability. The study highlights the potential of a fully digital workflow in modern prosthodontics, emphasizing its role in achieving more predictable outcomes, enhancing clinical efficiency, and reducing the need for post-cementation adjustments. Future research should explore.